'Casting' nanoporous nanowires: revitalizing the ancient process for designing advanced catalysts. Issue 22 (23rd May 2018) - Wang, Ying; Kou, Tianyi; Gao, Hui; Niu, Jiazheng; Zhang, Jie; Lv, Lanfen; Peng, Zhangquan; Zhang, Zhonghua
Abstract : Novel eutectic-directed self-templating strategy is proposed to 'cast' PdPtNi nanoporous nanowires with superior bifunctional catalytic activity to both EGOR and GOR. Abstract : Eutectic reaction frequently occurs in metallurgical solidification of alloy melts, and has been widely studied for traditional structural and engineering applications for decades. Here, we inject new blood into this ancient process and develop its novel application in the general preparation of advanced nanostructured materials. Based upon solidification control and dealloying inheritance effect, we 'cast' advanced M (M = Pt, Pd or PdPt)–Ni nanoporous nanowires (NPNWs) via a novel eutectic-directed self-templating strategy. The PdPtNi NPNWs exhibit impressively enhanced electrocatalytic performance towards ethylene glycol and glycerol electrooxidation in an alkaline electrolyte compared to commercial Pt/C (40 wt%), as evidenced by enhanced electrocatalytic activity, better anti-poisoning property and stability. The superior electrocatalytic performance of PdPtNi NPNWs originates from its unique nanoporous nanowire network structure, alloying effect of Ni, modified electronic states of Pd/Pt and synergistic interactions between Pt, Pd and Ni.